EVALUATION OF FERMENTED FOOD DIGESTION OF LIGNOCELLULOLYTIC PROBIOTIC BACTERIA IN THE END-STAGE FERMENTATION MACHINE - I. I., Khoiron; Mudita, I M.; Candrawati, D.P.M.A. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
This study was conducted to determine the effect of fermented rations using fermental probiotic bacteria on the digestibility of broiler chickens. This research was conducted from April to June 2021 at the teaching farm of the College of Animal Husbandry, Udayana University, Bali. This study used 60 broiler chickens. The research design used was a completely randomized design (CRD) consisting of 5 coefficients and 4 replicates. Each repetition consists of 3 broiler hens. The treatment was given fermented rations without probiotic (BRF0) as a control, and rations fermented with Bacillus subtilis BR4LG (BRF1), Bacillus sp. BT3CL (BRF2), Bacillus sp. BT8XY (BRF3) and commercial rations (BRK) were used as a control using cell lysate probiotics up to 5% of the total feed ingredients. The variables observed were dry matter digestibility, organic matter, crude fibre, crude protein, crude fat, and apparent energy metabolism. Obtained data were analyzed using variance, if there was a difference (P < 0.05), analysis was continued with Duncan's multiple-distance test. The results showed that the batch containing BRF3 treatment had the best quality among the other treatments followed by BRF0, BRF1 and BRF2. The digestibility of organic matter, crude fiber and crude fat was higher in the treatment with fertolytic probiotics than without the fetoprobiotics. The digestibility of the crude protein treated with BRF2 and BRF3 was higher than that of BRF0 and BRF1. The apparent metabolic energy of BRF1 and BRF3 is higher than that of BRF2 and BRF0.   Keyword s : Ration, digestible, probiotic,broiler